ISLAM DAN SAINS PERSPEKTIF NURCHOLISH MADJID - Helmy Hidayatulloh (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This article explains the relationship between Islam and science from the perspective of Nurcholish Madjid. Nurcholish saw the relationship between Islam and science through two things, namely: first, the contribution of Islam to science; and second, the organic unity of Islam and science. Islam contributes greatly to the development of science and the contribution of Islam really cannot be underestimated because Islam is able to influence almost all fields of scientific studies. In addition, Islam has an organic and harmonious relationship with science. According to Nurcholish, science will always have a positive impact on a Muslim's faith, but if his faith is true. Conversely, if the faith is wrong, then the faith will be filled with things that are mythological. If a belief is filled with mythology, then the belief (religion) will be defeated by science.